DEVELOPMENT OF MESOPOROUS SILICA NANOPARTICLE (MSN) LOADED CELECOXIB WITH HISTIDINYLATED POLY-L-LYSINE BASED GATEKEEPER - Natalie Xeliem, Jovinka
Celecoxib is a drug belongs to the Non-Steroidal Anti-Inflammatory Drugs (NSAID) group, commonly used to manage chronic inflammation and consumed over a long period of time. Long-term use of the drug can lead to a decrease in patient compliance with daily medication intake. One way to address this issue is by creating a sustained-release formulation. Previous research has shown that Mesoporous Silica Nanoparticles (MSN) can be surface-modified to be used as sustained-release formulations. MSNs are generally modified with gatekeepers such as Poly-L-Lysine (PLL). Other research indicates that histidinylated PLL can increase the amount of drug released from MSN. This study includes the synthesis of MSN and its functionalization with amine groups, drug entrapment into nanoparticles, creation of Poly-L-Lysine-Histidine (PLL-His) gatekeepers, and their conjugation to MSN. The synthesized MSNs were characterized using several instruments and subjected to in vitro release tests at pH 1.2 and pH 7.4. Thermogravimetric analysis (TGA) results showed a greater %weight loss reduction in MSNs with gatekeepers compared to MSNs without gatekeepers. All MSNs and their modifications had particle sizes <300 nm and polydispersity indexes <0.5. MSNs could entrap celecoxib with an efficiency of 23.35 ± 0.39% and a capacity of 23.54 ± 0.42%. Release tests showed that MSN conjugated with gatekeepers could protect the drug from being released at stomach pH (pH 1.2) and ensure slow drug release at the absorption site pH (pH 7.4). Drug release from MSN with PLL-His gatekeepers also showed a significant increase (p-value <0.05) compared to MSN with PLL gatekeepers.